Diversity, phylogeny and expression patterns of Pou and Six homeodomain transcription factors in hydrozoan jellyfish Craspedacusta sowerbyi - Hroudova, Miluse; Vojta, Petr; Strnad, Hynek; Krejcik, Zdenek; Ridl, Jakub; Paces, Jan; Vlcek, Cestmir; Paces, Vaclav (PloS one, 2012)
Formation of all metazoan bodies is controlled by a group of selector genes including homeobox genes, highly conserved across the entire animal kingdom. The homeobox genes from Pou and Six classes are key members of the regulation cascades determining development of sensory organs, nervous system, gonads and muscles. Besides using common bilaterian models, more attention has recently been targeted at the identification and characterization of these genes within the basal metazoan phyla. Cnidaria as a diploblastic sister group to bilateria with simple and yet specialized organs are suitable models for studies on the sensory organ origin and the associated role of homeobox genes. In this work, Pou and Six homeobox genes, together with a broad range of other sensory-specific transcription factors, were identified in the transcriptome of hydrozoan jellyfish Craspedacusta sowerbyi. Phylogenetic analyses of Pou and Six proteins revealed cnidarian-specific sequence motifs and contributed to the classification of individual factors. The majority of the Craspedacusta sowerbyi Pou and Six homeobox genes are predominantly expressed in statocysts, manubrium and nerve ring, the tissues with sensory and nervous activities. The described diversity and expression patterns of Pou and Six factors in hydrozoan jellyfish highlight their evolutionarily conserved functions. This study extends the knowledge of the cnidarian genome complexity and shows that the transcriptome of hydrozoan jellyfish is generally rich in homeodomain transcription factors employed in the regulation of sensory and nervous functions.
Keywords: Animals; orgánová specificita; Female; Protein Structure, Tertiary; POU Domain Factors; ženské pohlaví; faktory domény POU; terciární struktura proteinů; Evolution, Molecular; molekulární evoluce; Hydrozoa; Genetic Variation; Phylogeny; Organ Specificity; transkriptom; zvířata; Transcriptome; fylogeneze; genetická variace